The Content Validity and Reliability of Injury Severity Parameters in Data Collection Tool for Developing a National Trauma Prognostic Scale (TPS) - Jalilvand , Hadi; Sadeghi-Bazargani, Homayoun; Meshkini, Mohammad; Abdi , Mojtaba; Saadati , Mohammad (Shahroud Journal of Medical Sciences, 2023)
Background: Trauma injuries are a health threat to the whole world and according to 2016 WHO report, are one of the top ten causes of death. This study aimed to determine the content validity and inter-rater reliability of a data collection tool used to develop a national Trauma Prognostic Scale (TPS).Methods: The study was conducted in three stages including the development of the primary tool, assessment of the validity tool, and assessment of the reliability. The content validity, inter-rater reliability, and intra-rater reliability were assessed. For reliability assessment, 45 trauma patients from three trauma specialty centers in Tehran and Tabriz metropolises participated in the study.Results: The final data collection tool had a total of 51 items in six parts as demographic (part A with 9 items); past medical history (part B with14 items); type of patients’ transferring (Part C with 3 items); pre-hospital measures (part D with 9 items); physiological indicators of injury severity (part E with 9 items), and anatomical indicators of injury severity (part F with 7 items). The content validity of the tool was confirmed with a total scale-level content validity (S-CVI) = 0.93, S-CVI= 0.92 for part A, S-CVI= 0.90 for part B, S-CVI= 1.000 for part C, S-CVI= 0.90 for part D, S-CVI= 0.95 for part E, and S-CVI= 0.91 for part F. Spearman correlation was above 0.7 for all items.Conclusions: The content validity, and inter-rater test-retest reliability of the data collection tool for the developed TPS was confirmed.Keywords: Trauma, Injury, Prognostic, Validity, Reliability